JetStream Rotational and Aspiration Atherectomy in Treating In-Stent Restenosis of the Femoropopliteal Arteries: Results of the JETSTREAM-ISR Feasibility Study. (April 2016) - Shammas, Nicolas W.; Shammas, Gail A.; Banerjee, Subhash; Popma, Jeffrey J.; Mohammad, Atif; Jerin, Michael
Purpose: To evaluate the outcomes and stent-device interaction of the JetStream atherectomy device in the treatment of in-stent restenosis (ISR) of the femoropopliteal segment.Methods: The JetStream XC atherectomy device, a rotational cutter with aspiration capacity, was evaluated in a prospective cohort of 29 patients (mean age 69.9±11.7 years; 11 men) with femoropopliteal ISR in 32 limbs ( ClinicalTrials.gov identifier NCT01722877). Lesion length was 17.4±13.1 cm. The primary effectiveness outcome was acute success (≤30% residual narrowing with no serious adverse events). The primary safety endpoint was major adverse events. Secondary endpoints included clinically driven target lesion revascularization (TLR) at 6 months and 1 year and loss of stent integrity as assessed by an angiographic core laboratory.Results: Treated length was 19.5±12.9 cm. Acute success was obtained in 29/32 (91%) limbs. Acute device success (<50% residual narrowing after atherectomy alone) was 76% (22/29). Adjunctive balloon angioplasty was performed in all cases at a mean pressure of 11.6±3.3 atm. Embolic filter protection was used in 16 (50%) of 32 limbs. Macrodebris was noted in 2 (12%) of 16 filters. Distal embolization requiring treatment occurred in 3/32 (9.4%) limbs (2 with no filter). Other non-procedure-related adverse events were 1 (3%) death (nonvascular) and 1 (3%) case of major bleeding. There were no new stent fractures or deformities (n=24) postatherectomy. Follow-up was completed on 27 patients (29 limbs) at 6 and 12 months. TLR at these time points occurred in 4/29 (14%) and 12/29 (41%) patients. Patency (duplex-derived peak systolic velocity ratio <2.4) was 72% at 6 months.Conclusion: JetStream atherectomy using the XC device has favorable acute results in treating femoropopliteal ISR with high procedure success, no device-stent interaction, and favorably low TLR rates. A multicenter trial is needed to confirm these results.